Estimation of the uterine integrity in Chilean purebred mares and its association with age and foaling number - Morales Muñoz, Pamela Carolina (2018)
The objective of this study was to evaluate the uterine integrity of Purebred Chilean mares in relation to age and parity number. A total of 30 mares stratified according to age (young: 2-12 years, elder: >12 years) and parity (0, 1-2,> 2 parturitions). The integrity of the cervix was evaluated, and biopsies were performed for cytology and microbiological culture of the endometrium. Results showed that 73.3% of the mares had histopathological alterations without statistical association with age and parity. The uterine cytology showed that 43.3% of the mares had endometritis, a condition that showed significant association with age and parity. Escherichia coli was isolated in 8 of the 10 cases of bacterial endometritis of the study. Also, 13 mares presented abnormalities of the cervix, which was associated with age and parity. The results indicated that the age and parity number are factors that should be considered when evaluating the potential fertility of Purebred Chilean Mares.